Nanofabrication yields. Hybridization and click-fixation of polycyclic DNA nanoassemblies. - Lundberg, E; Plesa, C; Wilhelmsson, L; Lincoln, P; Brown, T; Nordén, B (2011)
We demonstrate the stepwise assembly of a fully addressable polycyclic DNA hexagon nanonetwork for the preparation of a four-ring system, one of the biggest networks yet constructed from tripodal building blocks. We find that the yield exhibits a distinct upper level <100%, a fundamental problem of thermodynamic DNA assembly that appears to have been overlooked in the DNA nanotechnology literature. A simplistic model based on a single step-yield parameter y can quantitatively describe the total yield of DNA assemblies in one-pot reactions as Y = y(duplex)(n), with n the number of hybridization steps. Experimental errors introducing deviations from perfect stoichiometry and the thermodynamics of hybridization equilibria contribute to decreasing the value of y(duplex) (on average y = 0.96 for our 10 base pair hybridization). For the four-ring system (n = 31), the total yield is thus less than 30%, which is clearly unsatisfactory if bigger nanoconstructs of this class are to be designed. Therefore, we introduced site-specific click chemistry for making and purifying robust building blocks for future modular constructs of larger assemblies. Although the present yield of this robust module was only about 10%, it demonstrates a first step toward a general fabrication approach. Interestingly, we find that the click yields follow quantitatively a binomial distribution, the predictability of which indicates the usefulness of preparing pools of pure and robust building blocks in this way. The binomial behavior indicates that there is no interference between the six simultaneous click reactions but that step-yield limiting factors such as topological constraints and Cu(I) catalyst concentration are local and independent.